2016
DOI: 10.14260/jemds/2016/1592
|View full text |Cite
|
Sign up to set email alerts
|

Candidal Balanoposthitis – A Retrospective Study in a Tertiary Care Centre of South India

Abstract: BACKGROUNDCandidal balanoposthitis is a known clinical marker and most of the time it may be the presenting feature of diabetes mellitus. It is the most common condition in uncircumcised male patients attending the sexually transmitted infections (STI) clinic in recent times as there is a decline in the tropical sexually transmitted infections.The aim of this study is to determine the prevalence of candidal balanoposthitis in patients attending the STI clinic of a tertiary care centre. MATERIALS AND METHODSA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…[ 17 ] had reported that balanitis could be associated with 12% of newly diagnosed diabetics. According to the study conducted by Swamiappan et al .,[ 18 ] 47.22% of patients with candida balanoposthitis were known diabetic and 43.52% were newly diagnosed with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] had reported that balanitis could be associated with 12% of newly diagnosed diabetics. According to the study conducted by Swamiappan et al .,[ 18 ] 47.22% of patients with candida balanoposthitis were known diabetic and 43.52% were newly diagnosed with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases that result in genital ulcerations are rare in children, making the diagnosis of these conditions difficult. Candidal balanitis typically affects sexually active adult males and may present as eroded papules, pustules, whitish discharge or erythema with dry glazed appearance 1 . Candidal balanitis usually affects sexually active males who have sexual partners with vaginal candidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Candidal balanitis typically affects sexually active adult males and may present as eroded papules, pustules, whitish discharge or erythema with dry glazed appearance. 1 Candidal balanitis usually affects sexually active males who have sexual partners with vaginal candidosis. Genital lesions due to candidiasis have been reported infrequently in children.…”
Section: Case Reportmentioning
confidence: 99%
“…Ведущее значение в развитии кандидоза кожи и его частного про-явления в виде кандидозного баланопостита имеет иммуносупрессия вследствие нерационального применения антибиотиков, кортикостероидов, гормональных контрацептивов и т.д. [6,7]. Обзор литературы демонстрирует важность других возбудителей в этиологии инфекционных баланопоститов -аэробов (Staphylococcus aureus, Streptococcus Group A) и анаэробов (Pseudomonas spp., Gardnerella spp., Bifidobacterium spp.…”
unclassified